The effect of pelvic floor muscle training in urinary incontinent elderly women: a sistematic review - Raquel Henriques Jácomo; Fátima Fani Fitz; Aline Teixeira Alves; Isabella Silveira Fernandes; Fellipe Amatuzzi Teixeira; João Batista de Sousa
Introduction The International Continence Society (ICS) determines that the pelvic floor muscles training (PFMT) is the first-choice treatment of urinary symptoms in women. Objective The aim of this study was to systematize randomized controlled clinical trials that address the effects of PFMT in the treatment of urinary symptoms in older women using objective outcome measures. Method Systematic review search was performed eletronic the following databases: Medline, Pubmed, Lilacs, PEDro and manual research conducted in the references of the studies. Were considered eligible women aged over 60 years who performed PFMT in isolation, without the involvement of another technique. The PFMT performed in clinic or at home, with or without the supervision of a therapist and with or without the use of biofeedback as an adjunct. Considered as outcome measures urodynamic studies, voiding diary that assesses daytime urinary frequency, nocturnal urinary frequency, urinary incontinence and exchange absorbent, and, finally, the absorbent test that quantifies loss urinary grams. The assessment of methodological quality of the studies was conducted by PEDro scale. Results Three studies were reviewed in full. Only one trial was rated high methodological quality. There was significant improvement in urinary symptoms after treatment proposed in the three selected studies. Conclusion Considering the studies available so far are weak the evidence for the use of PFMT in the treatment of urinary symptoms in elderly women.